To live or let die? An empirical analysis of piecemeal voluntary corporate liquidations - Erwin, Gayle R.; McConnell, John J. (Journal of Corporate Finance, 1997)
This paper is an in-depth investigation of 61 publicly-traded firms that chose to liquidate voluntarily on a piecemeal basis during the 1970s and 1980s. In comparison with their industry peers, these firms have lower Tobin's Q, a higher percentage of equity ownership by management and the board, a higher incidence of a member of the corporation's founding family in a key executive position or on the board, and a higher incidence of asset sales and prior attempts to transfer control of the firm. The average excess stock return of 20% around liquidation announcements is positively correlated with the fraction of stock owned by management and the board. These results suggest that firms that make the value enhancing decision to voluntarily liquidate confront low future growth opportunities, but the absence of future growth opportunities is not sufficient to bring about this decision. It is also necessary that decision makers have a vested interest in the outcome, either because of their ownership stake or because of their family affiliation with the business, and that the valuation consequences of the decision are greater, the more closely aligned are managerial and shareholder interests.